First observation of [Pu6(OH)4O4]12+ cluster during the hydrolytic formation of PuO2 nanoparticles using H/D kinetic isotope effect. Issue 94 (9th November 2022) - Cot-Auriol, Manon; Virot, Matthieu; Dumas, Thomas; Diat, Olivier; Menut, Denis; Moisy, Philippe; Nikitenko, Sergey I.
Abstract : New insights are provided about the formation mechanism of PuO2 nanoparticles (NPs) by investigating an unprecedented kinetic isotope effect observed during their hydrolytic synthesis in H2 O or D2 O media. Abstract : New insights are provided about the formation mechanism of PuO2 nanoparticles (NPs) by investigating an unprecedented kinetic isotope effect observed during their hydrolytic synthesis in H2 O or D2 O and attributed to OH/OD zero point energy difference. The signature of a Pu(iv ) oxo–hydroxo hexanuclear cluster, appearing as an important intermediate during the formation of the 2 nm PuO2 NPs (synchrotron SAXS/XAS), is further revealed indicating that their formation is controlled by H-transfer reactions occurring during hydroxo to oxo-bridge conversions.